ANALISIS PENERAPAN SIX SIGMA UNTUK MENINGKATKAN KUALITAS PADA PRODUKSI SPRING COIL - Angelo, William; Kosasih, Wilson; Doaly, Carla Olivia (Jurnal Mitra Teknik Industri, 2023)
Quality control of spring coil products has not been carried out properly, where it is indicated that most defects are outside control limits. This research was conducted at a company engaged in manufacturing, especially spring coils. The aim of this research is to increase process capability by reducing process variations that occur. The method used is Six Sigma DMAIC. A Cp value of 0,8 was obtained, which was in the range Cp < 1 so that it could be concluded that the process capability value was still below and improvements needed to be made so that the Cp was close to 1. Then a DPMO value of 8173,721 was obtained with a sigma value of 3,901. From the analysis conducted, it was found that the main cause of the defect was that the gears had chipped/worn out and the bolt settings had changed. Therefore, suggestions for preventive card maintenance were carried out. The next proposal is a raw material control card to control the quality of raw materials from suppliers. Another action that can be taken is to calculate the DPMO on a monthly basis. This is done to control the ongoing production process. The last proposal is with the 5S/5R kaizen plan card, which is to introduce that small changes can have a positive impact on sustainable change. With these proposals, the problems that occur, namely defects that are still high, can be reduced. Therefore this company needs to exercise control to maintain the suggestions that have been given or even improve them more than before.